1991
DOI: 10.1152/ajpgi.1991.260.6.g795
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyamines in gastrointestinal mucosal growth

Abstract: The polyamines have been under active investigation for nearly three decades. There is a great deal of evidence that they play an important role in gastrointestinal mucosal growth, but the mechanisms through which this role is carried out are still not fully explained. This review examines the role of the polyamines in the regulation of mucosal growth, the control of intracellular polyamine levels, the biosynthesis of the polyamines, and some known mechanisms of their action. Finally, we propose a model of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 0 publications
1
110
0
1
Order By: Relevance
“…Several mechanisms for controlling this adaptive response have been postulated, including the effect of bacterial metabolic products, physical characteristics of luminal content, and systemic factors (hormonal and neural) (22,33,55). The evidence from different studies regarding the principle factor(s) involved is often conflicting, suggesting that there are multiple factors that interact to control colonic mucosal growth characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms for controlling this adaptive response have been postulated, including the effect of bacterial metabolic products, physical characteristics of luminal content, and systemic factors (hormonal and neural) (22,33,55). The evidence from different studies regarding the principle factor(s) involved is often conflicting, suggesting that there are multiple factors that interact to control colonic mucosal growth characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have failed to show that high-fat diets elevate colonic bile acid concentration (9,17) in rats or increase epithelial cell proliferation in the colon (26,27,31,52). Other bacterial metabolites, such as ammonia and polyamines, have also been implicated in influencing mucosal growth (33,56).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of cellular polyamines is thought to be a central convergence point for the multiple signaling pathways driving epithelial cell function. We (6, 8 -14) and others (1,5,15) have demonstrated that normal epithelial cell proliferation in the intestinal mucosa depends on the supply of polyamines to the dividing cells and that decreasing cellular polyamines inhibits epithelial cell proliferation by stabilizing the mRNAs that encode nucleophosmin (NPM), 3 p53, and other growth-inhibiting factors. However, the exact mechanisms whereby polyamine depletion stabilizes NPM and p53 mRNAs remain elusive.…”
mentioning
confidence: 99%
“…In addition, probiotic products are important mediators of cell growth and differentiation and prevent lipid peroxidation in liver microsomes. [25,26] Our findings suggest that dual-coated and uncoated probiotic supplements may exhibit hepatoprotective effects by affecting the oxidative stress levels and TNF-a.…”
Section: Parametersmentioning
confidence: 80%